Developing Powerful Athletes Part 2: Practical Applications. Issue 1 (February 2021) - Turner, Anthony N.; Comfort, Paul; McMahon, John; Bishop, Chris; Chavda, Shyam; Read, Paul; Mundy, Peter; Lake, Jason
Abstract : ABSTRACT: In part 1 of this two-part review, we addressed the recent criticisms of the use of terms such as power, rate of force development, and explosiveness, over impulse. These terms were distinguished mechanically and conceptually for the benefit of the scientist and coach. In part 2, we use the key mechanical parameters underpinning power development and its relationship with the force–time characteristics and force–velocity profile of sporting movements, to evidence the planning of training drills and assist the strength and conditioning coach in devising periodized training programs.